Pielęgnacja i usprawnianie osób z paraplegią i tetraplegią = Care and improvement of people with paraplegią and tetraplegią - Pietkun, Katarzyna; Siminska, Joanna; Stępowska, Justyna; Dejewska, Jolanta; Lewandowska, Anna; Porzych, Piotr; Nowacka, Krystyna; Beuth, Wojciech (Journal of Education, Health and Sport, 2016)
Pietkun Katarzyna, Siminska Joanna, Stępowska Justyna, Dejewska Jolanta, Lewandowska Anna, Porzych Piotr, Nowacka Krystyna, Beuth Wojciech. Pielęgnacja i usprawnianie osób z paraplegią i tetraplegią = Care and improvement of people with paraplegią and tetraplegią. Journal of Education, Health and Sport. 2016;6(8):427-438. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60794 http://ojs.ukw.edu.pl/index.php/johs/article/view/3778 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016. PIELĘGNACJA I USPRAWNIANIE OSÓB Z PARAPLEGIĄ I TETRAPLEGIĄ CARE AND IMPROVEMENT OF PEOPLE WITH PARAPLEGIĄ AND TETRAPLEGIĄ Pietkun Katarzyna1,2, Siminska Joanna1, Stępowska Justyna1, Dejewska Jolanta1, Lewandowska Anna1, Porzych Piotr1, Nowacka Krystyna1,4, Beuth Wojciech3,4 1 Katedra i Klinika Rehabilitacji Collegium Medicum w Bydgoszczy 2 Katedra Kosmetologii i Dermatologii Estetycznej Collegium Medicum w Bydgoszczy 3 Wojewódzki Szpital Specjalistyczny we Włocławku, 4 Kujawska Szkoła Wyższa we Włocławku Abstrakt Urazy kręgosłupa i rdzenia kręgowego stanowią problem leczniczy z uwagi na występujące po najczęściej wypadku poważne zaburzenia funkcji całego organizmu. Według danych statystycznych zjawisko występowania urazów kręgosłupa i rdzenia kręgowego częściej dotyczy mężczyzn niż kobiet oraz osób młodych między 16 a 30 rokiem życia. Analizując dane ponad połowa urazów powstaje podczas wypadków komunikacyjnych, następnie upadków z wysokości, urazów sportowych ale również jest wynikiem nieleczonej osteoporozy bądź nowotworów. Uraz najczęściej obejmuje odcinek szyjny rdzenia oraz rdzenia na pograniczu piersiowo-lędźwiowym. Późne następstwa urazów rdzenia kręgowego można przedstawić również jako zmiany w obrębie jakości życia. Na szeroko rozumianą jakość życia składają się: warunki mieszkaniowe, stan cywilny i rodzinny, sytuacja finansowa, kształcenie, zarobkowanie, uprawianie sportu i podejmowanie innych form rekreacji. Celem pracy jest przedstawienie jakości życia pacjenta po urazie kręgosłupa jak również elementów profilaktyki i rehabilitacji, możliwości powrotu pacjentów do aktywności życiowej sprzed urazu, jaki jest czas powrotu, jak na jakość życia wpływa wiedza o chorobie. Słowa kluczowe: uraz kręgosłupa, powikłania, pielęgnacja chorego, rehabilitacja. Summary Injuries to the spinal column and spinal cord are a medical problem due to the most frequently occurring case of severe disorders of the body. According to statistics the phenomenon of spinal injuries and spinal cord injury affects more men than women, and young people between 16 and 30 years old. Analyzing data on more than half of the injuries produced during traffic accidents, followed by falls from a height, sports injuries but also is the result of untreated osteoporosis or cancer. The injury usually involves the cervical core and the core on the border of the thoraco-lumbar region. Term effects of spinal cord injuries can be represented also as the change in the quality of life. On the wider quality of life include: housing, marital and family status, financial situation, learning, earning, playing sports and taking other forms of recreation. The aim of the study is to present the quality of life of the patient after the injury of the spine as well as the elements of prevention and rehabilitation, the possibility of returning patients to active life before the injury, what is the recovery time, as the quality of life affects the knowledge about the disease. Keywords: spinal injury, complications, patient care, rehabilitation.